The Needs Assessment Academic Administration in Special Education Service Centers under Office of Special Education Administration - Dangthongdee, Thamonwan; Sriiam , Supatcha; Wongsirasawat, Chanchai (Journal of Buddhist Education and Research (JBER), 2025)
The objectives of this research article are 1) to study the current level and the desired level of academic administration of special education center service units, Office of Special Education Administration, and 2) to study the needs of academic administration in special education service centers under office of special education administration. The samples used in the research were 322 teachers of special education centers, Office of Special Education Administration, the sample size was determined by Yamane’s sampling formula. The research instrument was a 5-point rating scale questionnaire with a reliability value of 0.99. The statistics used for data analysis were mean, standard deviation, and PNI modified. The research results found that 1) the current level of academic administration in special education service centers under office of special education administration Overall, it was at a high level for all 5 items (x ̅= 4.23, S.D. = 0.63). Desirable level of academic administration in special education service centers under office of special education administration Overall, it was at a high level (x ̅= 4.38, S.D. = 0.62). 2) Assessment of the needs of academic administration in special education service centers under office of special education administration, the order of needs are as follows: inclusive education, community-based rehabilitation, student registration measurement and evaluation transitional services, early intervention and facilities, media, services, and other educational assistance.